Full Stack iOS Development with Swift and Vapor Full stack iOS development made easy (English Edition) - Dutt, Hem; Dutt, Hem (BPB Publications, 2023)
A step-by-step journey into full-stack iOS development with Swift and Vapor Key Features ? Learn how to leverage Vapor to build robust backend systems for your iOS applications. ? Seamlessly integrate frontend and backend components in your full-stack iOS application. ? Learn to configure servers and successfully launch your app in a live environment. Description Full-stack iOS applications combine frontend and backend development to create powerful and versatile mobile experiences, providing users with rich functionality and reliable data management. If you're interested in building full stack iOS applications, this book is a perfect fit for you. To embark on your full stack iOS development journey, the book initiates by installing the Vapor Toolbox and Xcode, equipping you with essential tools for swift progress in constructing complete projects. Through a practical approach, the book will help you navigate the intricacies of routing, implementing security measures, seamlessly integrating data, managing data effectively, and generating server-side JSON responses. As you delve deeper into the book, your expertise will expand to encompass the vast ecosystem of iOS app development, including features such as UIKit with Auto-layout, SwiftUI, Core Data, and more. Furthermore, this book serves as your guiding companion, embracing the potential of comprehensive instruction and unveiling the secrets of successful full stack iOS development. It empowers you to unleash your capabilities by understanding the complexities of bridging backend and front-end technologies. With its extensive coverage, the guide empowers you to overcome obstacles such as data storage, performance optimization, and security. By providing you with the necessary expertise and resources, this book enables you to build impressive, secure, and scalable full stack iOS applications. What you will learn ? Learn the process of setting up a Vapor project, including routing, controller creation, and middleware implementation. ? Discover how to interact with databases using the Fluent ORM, defining models, and relationships, and performing CRUD operations. ? Learn how to design user interfaces using SwiftUI, implementing navigation and user interaction in your iOS app. ? Learn to effectively communicate with web services and APIs. ? Understand the process of deploying your full stack iOS application. Who this book is for This book is for aspiring developers, students, and experienced iOS developers who are skilled in Swift and looking to delve into full stack development. Table of Contents 1. Full-stack Development Overview 2. Setting Up the Environment 3. Routing, MVC and JSON in Vapor 4. Async and HTML Rendering in Vapor 5. PostgreSQL Integration in Vapor 6. Building User Interfaces for iOS 7. Data Persistence with Core Data and SQLite in iOS 8. Full Stack Implementation 9. Advanced Full-stack Concepts 10. Deploying iOS and Vapor Applications